Eliminating Edge Electronic and Phonon States of Phosphorene Nanoribbon by Unique Edge Reconstruction. Issue 2 (4th December 2021) - LI, Shi‐Qi; Liu, Xiangjun; Wang, Xujun; Liu, Hongsheng; Zhang, Gang; Zhao, Jijun; Gao, Junfeng
Abstract: Edge termination plays a vital role in determining the properties of 2D materials. By performing compelling ab initio simulations, a lowest‐energy U‐edge [ZZ(U)] reconstruction is revealed in the bilayer phosphorene. Such reconstruction reduces 60% edge energy compared with the pristine one and occurs almost without an energy barrier, implying it should be the dominating edge in reality. The electronic band structure of phosphorene nanoribbon with such reconstruction resembles that of an intrinsic 2D layer, exhibiting nearly edgeless band characteristics. Although ZZ(U) changes the topology of phosphorene nanoribbons, simulated transmission electron microscope, scanning transmission electron microscope and scanning tunneling microscope images indicate it is very hard to be identified. One possible identified method is infrared/Raman analyses because the ZZ(U) edge alters vibrational modes dramatically. In addition, it also increases the thermal conductivity of PNR 1.4 and 2.3 times than the pristine and Klein edges. Abstract : An unprecedented U‐edge [ZZ(U)] reconstruction with the lowest energy is predicted to occur easily in the bilayer phosphorene. The U‐edge reconstruction unexpectedly exhibits nearly edgeless characters for both electronic and thermal transport.